(untitled) (Eurasian Scientific Herald, 2026)
Chronic viral hepatitis B (CHB) remains a significant epidemiological and clinical challenge in the global healthcare system. According to the World Health Organization (WHO), more than 250 million people worldwide live with this infection, and approximately 800,000 deaths annually are associated with liver cirrhosis and hepatocellular carcinoma. In recent years, dietotherapy has been increasingly recognized as an important adjunct in the comprehensive management of liver diseases. This literature review aims to evaluate the impact of dietotherapy on clinical and laboratory parameters in patients with CHB. The findings indicate that dietotherapy serves as an important complementary component to antiviral therapy. However, methodological heterogeneity and a lack of long-term randomized controlled trials remain notable limitations in the existing literature